2017
DOI: 10.1007/s13361-017-1735-7
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Transmembrane Peptide Complexes to the Gas Phase Using Nanodiscs and Electrospray Ionization

Abstract: The gas-phase conformations of dimers of the channel-forming membrane peptide gramicidin A (GA), produced from isobutanol or aqueous solutions of GA-containing nanodiscs (NDs), are investigated using electrospray ionization-ion mobility separation-mass spectrometry (ESI-IMS-MS) and molecular dynamics (MD) simulations. The IMS arrival times measured for (2GA + 2Na) ions from isobutanol reveal three different conformations, with collision cross-sections (Ω) of 683 Å (conformation 1, C1), 708 Å (C2), and 737 Å (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Nanodiscs are a promising platform for native MS of membrane proteins due to their size, homogeneity, and relative monodispersity. To complement conventional detergent-based methods, nanodiscs allow membrane proteins to be delivered for native MS in a lipid bilayer environment, which may be a better model of the physiological environment of membrane proteins. Nanodiscs are nanoscale lipoprotein particles consisting of a lipid bilayer surrounded by two membrane scaffold protein (MSP) belts.…”
Section: Designing Mutant Membrane Scaffold Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanodiscs are a promising platform for native MS of membrane proteins due to their size, homogeneity, and relative monodispersity. To complement conventional detergent-based methods, nanodiscs allow membrane proteins to be delivered for native MS in a lipid bilayer environment, which may be a better model of the physiological environment of membrane proteins. Nanodiscs are nanoscale lipoprotein particles consisting of a lipid bilayer surrounded by two membrane scaffold protein (MSP) belts.…”
Section: Designing Mutant Membrane Scaffold Proteinsmentioning
confidence: 99%
“…Nanodiscs are nanoscale lipoprotein particles consisting of a lipid bilayer surrounded by two membrane scaffold protein (MSP) belts. There are a number of different MSP constructs available, but they are all derived from ApoAI, the primary component of high-density lipoprotein particles. Klassen and co-workers have employed nanodiscs with catch-and-release ESI to investigate glycolipid interactions with soluble proteins. ,,,,, , We showed that nanodisc complexes can be preserved intact for native MS, , and Robinson and co-workers later showed that nanodiscs can be used to deliver membrane protein complexes into the gas phase. , …”
Section: Designing Mutant Membrane Scaffold Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Marty et al [35] showed further that large numbers of lipids bound to the ejected proteins could still be detected, providing vital information about interactions within the lipid environment. In these and other studies, integral membrane proteins were co-assembled into nanodiscs and then released in the mass spectrometer, a 'build-and-release' approach [50,[55][56][57].…”
Section: Use Of Nanodiscs For the Study Of Peripheral Membrane Proteimentioning
confidence: 99%
“…Due to their relatively low polydispersity and high homogeneity, lipoprotein nanodiscs have emerged as a promising membrane mimetic for native MS. Nanodiscs have been used to deliver integral membrane proteins [8,11,12], peripheral membrane proteins [13,14], and transmembrane peptides [15] for native MS and to characterize large numbers of lipids bound to membrane protein complexes [16]. Recent work found that charge manipulation reagents enable a wide range of dissociation pathways, allowing the membrane protein to be either ejected from the nanodisc or characterized within a nearly intact nanodisc complex [17].…”
Section: Introductionmentioning
confidence: 99%